Pregnancy with severe anemia: a dangerous combination with increase in maternal and perinatal morbidity and mortality. How can we prevent it? - Tyagi, Smita; Tyagi, Natasha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Anaemia is a condition in which the number of red blood cells or their oxygen-carrying capacity is insufficient to meet physiologic needs, which vary by age, sex, altitude, smoking, and pregnancy status. In its severe form, it is associated with fatigue, weakness, dizziness and drowsiness. Pregnant women and children are particularly vulnerable. Methods: This study was carried out in the Department of Obstetrics and Gynecology, Muzaffarnagar medical college, Muzaffarnagar and the data was taken according to the WHO. Results: It was found that the prevalence of anemia was 91%. According to WHO classification, out of this 44.9% were mildly anemic, 29.9% were moderately anemic and 25% were severely anemic. Conclusions: The causes of anemia in pregnancy are illiteracy, poor socioeconomic status, improper distribution of iron and calcium tablets in rural areas due to poor health care intrastructure.